2015
DOI: 10.1007/s00280-015-2736-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of S-1 adjuvant chemotherapy for pancreatic cancer in elderly patients

Abstract: These results suggest that S-1 adjuvant chemotherapy for pancreatic cancer is safe and feasible, regardless of the age of the patient, especially for elderly patients who may be candidates for clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…ROC analysis showed that in PDAC prognosis evaluation (in combined datasets), this 6-mRNA signature was superior to age, histology grade and TNM stage. Many clinical parameters might affect the survival after PDAC surgery like histologic grade, TNM stage, serum CA19-9, perioperative blood transfusion, and metastasis to lymph nodes 43-49. To enhance prognostic prediction, 6-mRNA risk score was combined with age, histologic grade and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…ROC analysis showed that in PDAC prognosis evaluation (in combined datasets), this 6-mRNA signature was superior to age, histology grade and TNM stage. Many clinical parameters might affect the survival after PDAC surgery like histologic grade, TNM stage, serum CA19-9, perioperative blood transfusion, and metastasis to lymph nodes 43-49. To enhance prognostic prediction, 6-mRNA risk score was combined with age, histologic grade and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested that subtypes of gastric cancer may be important predictors for patients with gastric cancer who could benefit from chemotherapy. In clinical practice, oncologists are more likely to prescribe single agent chemotherapy for older patients or patients at earlier stage according to their physical condition [21, 22]. However, our result demonstrated that intensive two-drug chemotherapy regimen is better than mild chemotherapy in disease-free survival after curative resection with gastric cancer.…”
Section: Discussionmentioning
confidence: 73%
“…Patients 70 years and older are less likely to receive adjuvant chemotherapy although this treatment approach is associated with prolonged survival [26]. Aoyama et al reported that the safety and feasibility of S-1 adjuvant chemotherapy were similar between patients older than 70 years of age and those younger than 70 years of age [27]. In the JASPAC-01 trial [11], including participants aged 20 years or older, the median age of patients assigned to the S-1 arm was 66 (range, 60-73) years.…”
Section: Discussionmentioning
confidence: 99%